Literature Review on the Application of Interactive Media in Science Learning in Elementary Schools for the Period 2020-2025 - Prayoga, Bangkit Gigih; Wardani , Sri; Harniangsih , Harniangsih; Subali , Bambang; Widiati , Nuni (Journal of Educational Sciences, 2025)
This study aims to explore the application of interactive media in Science Education (IPA) for elementary schools from 2020 to 2025, focusing on its impact on student engagement, understanding, and learning outcomes. The research method used is a literature review, analysing 25 studies on the development and use of interactive media in teaching science concepts. The findings indicate that interactive media, such as animation videos, e-modules, augmented reality, educational games, and mobile applications, significantly improve student comprehension of complex science concepts by providing dynamic, visual, and engaging learning experiences. Moreover, these media foster greater student motivation and interest in learning, overcoming the limitations of traditional, teacher-centred methods. However, challenges remain, including unequal access to technology, readiness of teachers, and the need for curriculum adaptations. The study concludes that while interactive media is an effective tool for enhancing science education, further support is necessary from policymakers and educators to ensure its widespread and optimal use in elementary schools.